Antidiabetic Potential and Metabolite Profile of Leaf and Stem Extract of Castanopsis tungurrut (Blume) A.DC. - Bilqis Zahra Nabila; Muhammad Imam Surya; Intani Quarta Lailaty; Frisca Damayanti; Tri Rini Nuringtyas (Universitas Sebelas Maret, 2024)
Diabetes mellitus is a metabolic disorder caused by high blood sugar levels. One species in the Castanopsis genus is proven with a hypoglycemic effect. Therefore, the study aimed to discover the potential of Castanopsis tungurrut as an antidiabetic. Sample extraction, α-amylase inhibition, glucose diffusion analysis, GC-MS analysis, and molecular docking were applied in this study. Maceration of the leaf ethanol extract showed the highest yield value of 21.08%, while the stem extract was 14.04%. Leaf ethanol extract and stem ethyl acetate extract showed the highest inhibiting α-amylase activity with an inhibition value of 33.74%±1.54 and 34.45%±1.08 at 1 mg/mL concentration. The glucose entrapment assay showed that these two extracts could inhibit the diffusion of glucose in the dialysis bag. The final result was glucose concentration in dialysate for the two extracts of 0.114±0.001 mg/mL and 0.116±0.001 mg/mL which was lower than acarbose in 0.120±0.004 mg/mL. GC-MS analysis showed 6 metabolites in leaf ethanol extract and 22 metabolites in stems ethyl acetate extract from an alkane, salicylic, cinnamic, terpene, steroid, and fatty acid. Molecular docking resulting between the compounds with α-amylase enzymes complex showed γ-sitosterol and ß-bisabolene from C. tungurrut extract have the potential to be developed as an antidiabetic drug due to its good inhibitory activity with binding affinity values of -9.1 and -6.9 that considered better and quite close to acarbose as control of -7.7.